Efektivitas Sinkronisasi Estrus Menggunakan Hormon Prostaglandin dan Estrogen terhadap Non Return Rate (NRR), Conception Rate (CR) dan Service per conception (S/C) pada Sapi Potong - Jamili, Muhammad Arsan; Hardianto; Mappanganro, Rasyidah; Susanti, Handayani Indah; Lestari, Ayu; Hasrin (Jurnal Peternakan Lokal, 2025)
Prostaglandin and estrogen hormones are two types of hormones commonly used in estrus synchronization aimed at inducing earlier estrus in livestock. This study aims to evaluate the effectiveness of estrus synchronization using prostaglandin and estrogen hormones on Non Return Rate (NRR), Conception Rate (CR), and Service per Conception (S/C) in Beef Cattle. The research method is a field experiment, where female cattle are divided into several treatment groups based on the type of synchronization hormone used, namely P0 (natural estrus), P1 (prostaglandin injection), and P2 (estrogen injection). The parameters tested in this study are Non Return Rate (NRR), Conception Rate (CR), and Service per Conception (S/C). The data obtained were analyzed descriptively and calculated using the formulas for NRR, CR, and S/C. The results of this study show that the average NRR for the three treatments is 66.67%, with treatment P1 achieving the highest result of 83.33%, followed by P2 (66.67%) and P0 (50%). The highest CR was also obtained in treatments P1 and P2 with a percentage of 66.67%, while P0 was only 33.33%, with an overall average of 55.7%. For the S/C value, treatment P1 showed the highest efficiency with an average of 1.6 inseminations per pregnancy, followed by P2 (2.0) and P0 (3.33), with an overall average of 2, 31.